Preprodynorphin‐expressing neurons constitute a large subgroup of somatostatin‐expressing GABAergic interneurons in the mouse neocortex. Issue 7 (1st May 2014) - Sohn, Jaerin; Hioki, Hiroyuki; Okamoto, Shinichiro; Kaneko, Takeshi
ABSTRACT Dynorphins, leumorphin, and neoendorphins are preprodynorphin (PPD)‐derived peptides and ligands for κ‐opioid receptors. Using an antibody to PPD C‐terminal, we investigated the chemical and molecular characteristics of PPD‐expressing neurons in mouse neocortex. PPD‐immunopositive neuronal somata were distributed most frequently in layer 5 and less frequently in layers 2–4 and 6 throughout neocortical regions. Combined labeling of immunofluorescence and fluorescent mRNA signals revealed that almost all PPD‐immunopositive neurons expressed glutamic acid decarboxylase but not vesicular glutamate transporter, indicating their γ‐aminobutyric acid (GABA)ergic characteristics, and that PPD‐immunopositive neurons accounted for 15% of GABAergic interneurons in the primary somatosensory area. As GABAergic interneurons were divided into several groups by specific markers, we further examined the chemical characteristics of PPD‐expressing neurons by the double immunofluorescence labeling method. More than 95% of PPD‐immunopositive neurons were also somatostatin (SOM)‐immunopositive in the primary somatosensory, primary motor, orbitofrontal, and primary visual areas, but only 24% were SOM‐immunopositive in the medial prefrontal cortex. In the primary somatosensory area, PPD‐immunopositive neurons constituted 50%, 79%, 55%, and 17% of SOM‐immunopositive neurons in layers 2–3, 4, 5, and 6, respectively. Although SOM‐expressing neurons contained calretinin‐, neuropeptide Y‐, nitric oxide synthase‐, and reelin‐expressing neurons as subgroups, only reelin immunoreactivity was detected in many PPD‐immunopositive neurons. These results indicate that PPD‐expressing neurons constitute a large subgroup of SOM‐expressing cortical interneurons, and the PPD/SOM‐expressing GABAergic neurons might serve not only as inhibitory elements in the local cortical circuit, but also as modulators for cortical neurons expressing κ‐opioid and/or SOM receptors. J. Comp. Neurol. 522:1506–1526, 2014. © 2013 Wiley Periodicals, Inc.